A Look at the First Quarantined Community in the USA: Response of Religious Communal Organizations and Implications for Public Health During the COVID-19 Pandemic - Weinberger-Litman, Sarah L. (Journal of religion and health, 2020)
The current study examined anxiety and distress among members of the first community to be quarantined in the USA due to the COVID-19 pandemic. In addition to being historically significant, the current sample was unusual in that those quarantined were all members of a Modern Orthodox Jewish community and were connected via religious institutions at which exposure may have occurred. We sought to explore the community and religious factors unique to this sample, as they relate to the psychological and public health impact of quarantine. Community organizations were trusted more than any other source of COVID-19-related information, including federal, state and other government agencies, including the CDC, WHO and media news sources. This was supported qualitatively with open-ended responses in which participants described the range of supports organized by community organizations. These included tangible needs (i.e., food delivery), social support, virtual religious services, and dissemination of COVID-19-related information. The overall levels of distress and anxiety were elevated and directly associated with what was reported to be largely inadequate and inconsistent health-related information received from local departments of health. In addition, the majority of participants felt that perception of or concern about future stigma related to a COVID-19 diagnosis or association of COVID-19 with the Jewish community was high and also significantly predicted distress and anxiety. The current study demonstrates the ways in which religious institutions can play a vital role in promoting the well-being of their constituents. During this unprecedented pandemic, public health authorities have an opportunity to form partnerships with religious institutions in the common interests of promoting health, relaying accurate information and supporting the psychosocial needs of community members, as well as protecting communities against stigma and discrimination.